Exploring the effects of faecal microbiota transplantation on cognitive function: A review of clinical trials - Sara Alaeddin; Anushka Chatterjee; Tara L. Roberts; Genevieve Z. Steiner-Lim; Slade O. Jensen; Erika Gyengesi; Gerald Muench; Vincent Ho (Brain, Behavior, & Immunity - Health, 2025)
Faecal Microbiota Transplantation (FMT) is a widely used microbiota-modulation technique to treat recurrent Clostridioides difficile infections (rCDI). Rodent studies and clinical trials on probiotic interventions indicate that alterations in microbiota composition may impact cognitive function. To explore whether FMT influences cognitive function in humans, we conducted a systematic search and narrative synthesis and identified 14 studies examining its effects on cognition. A variety of cohort studies, single-arm trials, case reports and randomised, placebo-controlled trials have been conducted on different neurological patient cohorts, including those with Hepatic Encephalopathy, Parkinson's Disease, dementia, and Mild Cognitive Impairment. FMT has been shown to have a significant impact on cognitive function in these populations, accompanied by alterations in microbial composition and blood markers. Interestingly, success was influenced by the route of FMT administration, indicating greater efficacy of rectal cf. oral administration on microbiome composition and cognitive improvements. However, no clinical trials have yet examined the effects of FMT on cognitively healthy individuals. FMT appears to have potential as a therapeutic strategy for cognitive impairment, though further research with larger sample sizes is needed to explore its effects in both impaired and cognitively healthy populations.